Pengeringan Beku Vakum Bengkuang Dengan Memanfaatkan Panas Buang Kondensor Untuk Proses Sublimasi - Brama, Jaka; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Vacuum Freeze Drying  is one of the best ways of drying products as  freeze drying vacuum drying or  preserving  materials  without  a change in  physical and chemical properties  of materials.  This study was  a continuation of  previous  studies  that  vacuum  freeze drying jicama.  The results  of  previous studies  which  can  eliminate  62% moisture content  for 24 hours. This current research  is  to optimize the vacuum freeze drying previous  to adding  the heater exhaust condenser to the sublimation process.Condenser waste heat with temperatures reaching 40 ° C flowed dryer chamber and propagated on the  jicama to speed up the process of sublimation.Keyword: freeze drying vacuum, waste heat recovery condenser, jicama